Enhancing Strategic Positioning Through Marketing Engineering in Tourism Sector in Najaf City-Iraq - N. AL- Kulabi, Ameer; F. Abdulla, Daroon; S. Mohamad, Pirshing (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to identify the role of marketing engineering as an independent variable through its dimensions (marketing data and information, marketing insight, decisions, and implementation) in enhancing strategic position as a dependent variable by its dimensions (customer co-production, customer contact, and service customization). After reviewing the literature and conceptual framework, two main hypotheses were assumed to test the correlation and regression relationships between the study variables. An empirical study approach was utilized. This study was applied in the tourism organizations in Najaf city in Iraq. The study population consists of (233) managers in the hotels and tourism companies; the questionnaire was designed for collecting the data and was distributed to (178) directors, and only (163) of them returned it. Besides that, 46 questionnaires were excluded due to missing data. Hence, 117 questionnaires remained and were used in the statistical analysis using the statistical program (SPSS.V.20). The results showed a positive relationship and effect between the variables and their dimensions. Based on the results, a number of suggestions were given for the necessity for the tourism companies to practice the dimensions of marketing engineering in order to enhance their strategic positioning, and achieve sustainable competitive advantage. The contribution of this study can be realized in that this study was conducted in the tourism companies in the city of Najaf, which is considered one of the most cities across Iraq embracing tourists and visitors from the Middle East each year. In addition, no research has been found that examined the role of marketing engineering in enhancing strategic positioning.